Gestational age at birth and child special educational needs: a UK representative birth cohort study - Alterman, N; Johnson, S; Carson, C; Petrou, S; Rivero Arias, O; Kurinczuk, J; Macfarlane, A; Boyle, E; Quigley, M (BMJ Publishing Group, 2021)
Objective: To examine the association between gestational age at birth across the entire gestational age spectrum and special education needs (SEN) in UK children at 11 years of age.